Peningkatan Kapasitas Usaha Keripik Bayam Melalui Program Pembinaan UMKM di Lingkungan Sukaraja, Ampenan Tengah - Siti Nurliyana; Arni Aprillia; Hoerunnisa; Rani Surya Lestari; Eka Nurminda Dewi Mandalika (Jurnal Pengabdian Magister Pendidikan IPA, 2026)
This community service initiative aims to enhance the capacity and capabilities of spinach chip entrepreneurs in the Sukaraja neighborhood, Ampenan Tengah, Mataram City, through a structured and practical UMKM capacity-building program. The method used is a qualitative descriptive approach with a participatory approach, carried out from April to June 2026, covering the stages of preparation, survey, partner selection, technical training, and marketing assistance. Activities included business branding, packaging improvements, social media creation and management, as well as sales and promotional support, including participation in the “Bazar Jelajah Negeri Bangun Anti Korupsi” event as representatives of the Department of Commerce. The results of the activities showed a 25% increase in sales revenue and tangible improvements in product quality, more attractive and informative packaging, and more organized business management. Based on direct interviews, business owners stated that they felt greatly assisted; the use of social media and participation in the bazaar successfully expanded their market reach. Overall, this program succeeded in enhancing business owners’ capacity, building brand image, and supporting the sustainability of the spinach chip business in the local community.